Influence of soil on grounding system for substation - Ismail, Daut; Surya, Hardi; Risnidar Chan, Bahaudin (Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 2008)
Organized by Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 19-20 December 2006 at Batu Pahat, Johor.